(3SDGd Yf SHH hLhH ebGJdI GdQhGaVs - (3fhM GafOj GdMfajs
(3ChdgG (B:s
(3QaY Edi ehdGfG fhM CafOi GdMfai eG UhQJg (B: (3eG bhdce QVi Gddg JYGdi Yfce ai SHH hLhH ebGJdI GdQhGaV s
(3BNQgG (B:s
(3hjLhR ESJQbGb PQGQjge JHYkG dCegGJge (B,(3Gddg JYGdi CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi hGdYTQhfs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs